2000
DOI: 10.1071/pp99037
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal fluctuations in photoprotective (xanthophyll cycle) and photoselective (chlorophylls) capacity in eight Mediterranean plant species belonging to two different growth forms

Abstract: Xanthophyll cycle components and their pool sizes were seasonally examined in eight Mediterranean plant species from two different growth forms (drought semi-deciduals and evergreen sclerophylls), in an attempt to correlate possible fluctuations in the above parameters with potentially photoinhibitory conditions. The xanthophyll cycle was common in all species examined and was functional throughout the year. In semi-deciduals, the maximum midday values for conversion state, defined as the ratio (zeaxanthin + a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
2
15

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 25 publications
7
53
2
15
Order By: Relevance
“…Changes of NPQ process development in our case indicated that decrease of F v /F m was not due to photodamage and that heat dissipation process though still persistent under severe water stress is not fully functional. Under similar RWC, Kyparissis et al (2000) recorded the highest photoprotective potential (xanthophyll pool size) of mature P. fruticosa plants in the field. Therefore, seedlings appeared to be less efficient than the mature plants against the increased demand for thermal energy dissipation during severe water stress, but similar regarding recovery after re-watering (Kyparissis et al 2000, Montanaro et al 2007).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Changes of NPQ process development in our case indicated that decrease of F v /F m was not due to photodamage and that heat dissipation process though still persistent under severe water stress is not fully functional. Under similar RWC, Kyparissis et al (2000) recorded the highest photoprotective potential (xanthophyll pool size) of mature P. fruticosa plants in the field. Therefore, seedlings appeared to be less efficient than the mature plants against the increased demand for thermal energy dissipation during severe water stress, but similar regarding recovery after re-watering (Kyparissis et al 2000, Montanaro et al 2007).…”
Section: Discussionmentioning
confidence: 85%
“…In the present work we investigated PSII resistance to water stress in seedlings of the malacophyllous, dimorphic, semi-deciduous Mediterranean shrub Phlomis fruticosa L. Overall photosynthesis (gas exchange measurements), as well as ecophysiology of mature plants of P. fruticosa have been thoroughly investigated in our laboratory and a big repertoire of adaptations (morphological, biochemical and physiological) against adverse Mediterranean summer has been found (Grammatikopoulos and Manetas 1994, Grammatikopoulos et al 1995, Kyparissis et al 1997, Grammatikopoulos 1999, Karavatas and Manetas 1999, Kyparissis et al 2000. However, seedlings and young plants are expected to be more sensitive to water stress than their mature individuals (Fenner 1987, Padilla and Pugnaire 2007, Fotelli et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Such excess is partly related to the absorption of light and the capacity of a plant to use it in photosynthesis. Low A max together with a high chlorophyll concentration in the more exposed seedlings of Q. petraea is likely to increase such imbalance, triggering NPQ (Faria et al 1998;Kyparissis et al 2000;Martínez-Ferri et al 2000;Williams et al 2003). The rapid onset of NPQ suggested a higher sensitivity to elevated PPFD in Q. petraea.…”
Section: Discussionmentioning
confidence: 93%
“…The low plasticity detected for Xuorescence characters indicates that both the species maintain their photochemical eYciency by adjustments of other physiological characters, such as modiWcations of Quercus garrigue Quercus rock Pinus garrigue Pinus rock either photorespiration, pigment content or antioxidant capacity, especially in P. halepensis. This higher plasticity of P. halepensis for pigment and antioxidant characters could be related to the photoinhibition-avoiding strategy found in this species, since it would be a mechanism to reduce light absorption by PSII, dissipate excess energy and prevent overexcitation (Kyparissis et al 2000, Martínez-Ferri et al 2000. Phenotypic plasticity in response to water explained over 75% of the total variability among individual plants.…”
Section: Discussionmentioning
confidence: 95%